Clinical experience of uterine smooth muscle tumor of uncertain malignant potential in two gynecological centers: Oncological and obstetrical aspects. (March 2020) - Shim, Jung In; Han, Anthorny Kyung Woo; Jeon, Haeng Jun; Kim, Mi-La; Jung, Yong Wook; Yun, Bo Seong; Seong, Seok Ju; Shin, Eunah; Cho, Yeon Jean; Rha, Seo-Hee
Abstract: Objectives: To evaluate the clinical characteristics and obstetrical and oncological outcomes of patients with uterine smooth muscle tumors of uncertain malignant potential (STUMP) and analyze the risk factors for recurrence. Study Design: A retrospective cohort study was performed at two gynecological centers using data collected between January 2008 and August 2018. All the patients enrolled were diagnosed with STUMP and had been followed up for at least 6 months. The patients' characteristics, treatment methods, recurrence rate, and subsequent pregnancy outcomes were evaluated. Results: The mean age of the 62 patients was 36.1 ± 9.1 years (median 35, range 20–55 years) and mean follow-up duration was 36.3 ± 26.8 months (29.5, 6–130). All the patients were of premenopausal status. Fourteen patients (22.6 %) were initially treated by hysterectomy and 48 (77.4 %) by myomectomy. During the study period, three patients (4.8 %) experienced recurrence. However, there was no statistical difference between myomectomy and hysterectomy in terms of the rate of recurrence of STUMP or sarcoma, and all patients survived even after recurrence. Multivariate analysis revealed that a history of previous myomectomy was the sole independent risk factor for recurrence (odds ratio = 51.071; 95 % confidence interval = 2.743–950.726; p = 0.008). Subsequent pregnancies were successful in 10 of 19 women (52.6 %) who tried to conceive. Two of them had ongoing pregnancies at the time of last follow-up; the remaining eight women experienced a total of 14 subsequent pregnancies. Conclusions: The recurrence rate of STUMP was similar between hysterectomy and myomectomy. Therefore, fertility sparing myomectomy can be considered in women diagnosed with STUMP with close monitoring.